Impact of a 6-week foot tapping training program on lower limb strength, sprinting, jumping, and change of direction ability in soccer players - Chaabouni, S.; Al-Kiyoumi, W.: Fessi, M. S.; Methnani, R.; Al-Hadabi, B.; Kitani, M. A.; Al-Jadidi, K.; Moalla, W.; Gmada, N. (Journal of Sports Sciences, 2025)
This study aimed to evaluate the effects of a 6-week foot tapping training program (TAP-Training) on enhancing lower limb strength, sprinting, jumping, and change of direction ability in soccer players. Twenty-two soccer players were randomly assigned to either the TAP-Training group (TAP-TG, N = 11), which underwent the 6-week TAP-Training program, or the control group (CG, N = 11). Pre- and post-training assessments included jumps, sprints, the foot tapping test (TAP-test), and the change of direction test (MICOD), which were compared within and between groups. Significant improvements were observed post-training only in TAP score (p < 0.01) and MICOD performance (p < 0.05) within the TAP-TG. This indicates a positive impact of the neuromuscular frequency training program on TAP scores and change of direction performance. Conversely, no significant differences were noted in any parameters for the CG (p > 0.05) between pre-and post-training assessments. Furthermore, post-training comparisons between groups revealed statistically significant differences favoring the TAP-TG in TAP score and MICOD performance (p < 0.01). In conclusion, a 6-week TAP neuromuscular training program positively influences the change of direction performance and TAP scores in soccer players.